Changes in Body Composition and Cardiometabolic Health After Detraining in Older Men with Osteosarcopenia: 6-Month Follow-Up of the Randomized Controlled Franconian Osteopenia and Sarcopenia Trial (FrOST) Study - Kemmler W (Dove Medical Press, 2021)
Wolfgang Kemmler,1 Daniel Schoene,1 Matthias Kohl,2 Simon von Stengel1 1Institute of Medical Physics, Friedrich-Alexander University of Erlangen-Nürnberg, Erlangen, 91053, Germany; 2Faculty Medical and Life Sciences, University of Furtwangen, Villingen-Schwenningen, 78054, GermanyCorrespondence: Wolfgang KemmlerInstitute of Medical Physics, Friedrich-Alexander University of Erlangen-Nürnberg, Henkestrasse 91, Erlangen, 91052, GermanyTel +49 9131 8523999Fax +49 9131 8522824Email wolfgang.kemmler@imp.uni-erlangen.dePurpose: Temporary cessation of exercise but maintenance of habitual physical activity might be a frequent situation in older people’s lives. Particularly the COVID-19 induced lockdown of exercise training facilities with individual outdoor activities still being allowed might be a blueprint for this potentially harmful scenario. Thus, the aim of the present study was to determine the effects of 6 months of detraining after 18 months of high-intensity resistance exercise (HIT-RT) on body composition and cardiometabolic outcomes in predominately obese older men with osteosarcopenia.Materials and Methods: Community-dwelling predominately obese men 72– 91 years old with low muscle and bone mass (n=43) were randomly assigned to an 18-month HIT-RT (EG: n=21) or a non-training control group (CG, n=22). After the intervention, participants of the EG discontinued HIT-RT for 6 months, but increased their habitual physical activity. Study outcomes were group differences in detraining changes (“effects”) for lean body mass (LBM), total and abdominal body fat rate (determined by dual-energy x-ray absorptiometry) and the Metabolic Syndrome Z-Score (MetSZ). We applied an intention-to-treat analysis with multiple imputation to analyze the data.Results: After the 18-month HIT-RT, we observed significant positive training effects for LBM, total and abdominal body fat rate and the MetSZ (all p< 0.001). Abrupt cessation of HIT-RT for 6 months resulted in significantly higher unfavorable changes in the HIT-RT compared with the CG for LBM (p=0.001), total body fat (p=0.003) and the MetSZ (p=0.003), apart from abdominal body fat (p=0.059). However, significant overall effects were still present after 24 months for LBM and body fat indices but not for the MetSZ.Conclusion: The present study clearly indicates the unfavorable effects of 6 months of detraining after HIT-RT. Correspondingly, exercise protocols particularly for older people should focus on continuous exercise with short regeneration periods rather than on intermitted protocols with pronounced training breaks.Keywords: resistance exercise, detraining, lean body mass, body fat, metabolic syndrome, older men